Carbon storage potential of intensive silvopasture systems in humid tropics of kerala - Varsha K M (Academy of climate change education and research, 2016)
The research project entitled “Carbon storage potential of intensive silvopasture systems in humid tropics of Kerala” was carried out at Instructional Farm, College of Horticulture, Vellanikkara during 2013-2015, in existing 2 year old intensive fodder production systems, to assess their carbon storage potential and associated soil fertility changes. Comparative carbon storage efficiency of six different fodder production systems viz; 3-tier hybrid napier (HN)+ mulberry+ stylosanthus system, 2-tier HN+ mulberry/ stylosanthus systems and HN/ mulberry/ stylosanthus monoculture systems and one open plot with natural grass vegetation as absolute control was assessed in randomized block design replicated thrice. The 3- tier silvopastoral system consisted of grass, trees and herbaceous legumes in 3:1:1 ratio, 2- tier systems contained grass + tree/ legume in 3: 2 ratios on area basis, whereas the entire area contained either grass or legume or tree for monoculture treatments. Trees were planted at a high density (11111 trees ha-1) at 60 cm x 60 cm spacing and maintained as hedges of 1m height by harvesting at 3 months interval. All other crops were planted and harvested as per state recommendation. Fodder yields from various systems and carbon storage in plant biomass and soil was assessed for two years. Among various systems, mulberry monoculture captured the maximum carbon (211.23 Mg ha-1); 81% of which form permanent carbon stored in standing, root biomass and soil and 19% as labile carbon in harvested biomass. The second best system was 2-tier HN + mulberry (177.14 Mg ha-1), which captured 13 % more carbon than 3-tier silvopasture and HN monoculture systems. However, despite the higher carbon storage potential of mulberry monoculture, the fodder yields were significantly lower than HN+mulberry system. HN monoculture outyielded all other systems in fodder production, but carbon storage was comparatively poor. Hence, considering the fodder production efficiency and carbon storage capacity, 2-tier HN+mulberry system was found to be the most promising system for meeting both farmer needs and environmental services. Moreover, higher protein content in mulberry adds to the quality of the forage, which is an important factor in economic milk production. Variations in soil physical properties and nutrient status were assessed after two years. In general, soil physical properties were favourably influenced by tree based systems as compared to others.The least and comparable bulk density (1.45 g cm-3) was recorded in HN+mulberry and HN monoculture system. Soil pH and water holding capacity considerably improved in mulberry monoculture (7.283) followed by 2-tier HN+mulberry system (6.36). Soil temperature was also higher in tree based systems. The 3-tier systems were found to be superior to monoculture systems but inferior to 2-tier HN+mulberry system with respect to soil physical properties.Comparing the soil nutrient status, the total N, P, K and available P content was higher in stylosanthus based systems, whereas the available N and K content excelled in mulberry based systems. Hence, 3-tier HN+mulberry+stylosanthus system seemed more favourable for replenishing soil fertility as well as nutrient availability. However, stylosanthus being a poor fodder yielder, substituting it with a suitable high yielding leguminous fodder tree can take care of both the forage yields as well as the soil fertility aspects. To conclude,the current research brings out the suitability of intensive silvopasture systems with high yielding grass species (HN) and densely planted fodder tree hedges (mulberry @ 11111 trees ha-1), for maximizing quality fodder production and carbon sequestration and favourably influencing soil physical properties in humid tropics of Kerala. However, the above system could not contribute much to soil fertility owing to the non leguminous and exhaustive feeding behaviour of mulberry and HN. Hence, inclusion of a leguminous fodder tree along with mulberry and HN can take care of both the forage yields as well as the soil fertility improvement.